Monetary Integration in Europe in the Function of Fostering International Business (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2015)
Through joining the European Economic and Monetary Union a heterogeneous influence of member states cannot be avoided but all countries follow the logic of the economic benefits of unification. Besides reducing transaction costs, greater transparency in prices and the elimination of the uncertainty of exchange rate fluctuations, there is a great impact of open borders on increasing trade between member states. Therefore in this article we will analyze the Andrew Rose effect which estimated that countries with same currency trade over three times as much with each other as countries with different currencies. Through objective and systematic analysis we well conclude that the positive effect of monetary integration on increasing of international trade should be carried out in absolute and relative terms.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.